Rats Genetically Selected for High Aerobic Exercise Capacity Have Elevated Plasma Bilirubin by Upregulation of Hepatic Biliverdin Reductase-A (BVRA) and Suppression of UGT1A1 - Terry D. Hinds; Justin F. Creeden; Darren M. Gordon; Adam C. Spegele; Steven L. Britton; Lauren G. Koch; David E. Stec (MDPI AG, 2020)
Exercise in humans and animals increases plasma bilirubin levels, but the mechanism by which this occurs is unknown. In the present study, we utilized rats genetically selected for high capacity running (HCR) and low capacity running (LCR) to determine pathways in the liver that aerobic exercise modifies to control plasma bilirubin. The HCR rats, compared to the LCR, exhibited significantly higher levels of plasma bilirubin and the hepatic enzyme that produces it, biliverdin reductase-A (BVRA). The HCR also had reduced expression of the glucuronyl hepatic enzyme UGT1A1, which lowers plasma bilirubin. Recently, bilirubin has been shown to activate the peroxisome proliferator-activated receptor-α (PPARα), a ligand-induced transcription factor, and the higher bilirubin HCR rats had significantly increased PPARα-target genes Fgf21, Abcd3, and Gys2. These are known to promote liver function and glycogen storage, which we found by Periodic acid-Schiff (PAS) staining that hepatic glycogen content was higher in the HCR versus the LCR. Our results demonstrate that exercise stimulates pathways that raise plasma bilirubin through alterations in hepatic enzymes involved in bilirubin synthesis and metabolism, improving liver function, and glycogen content. These mechanisms may explain the beneficial effects of exercise on plasma bilirubin levels and health in humans.